Benevolent Leadership: Conceptualization and Construct Development - Karakas, Fahri (Journal of business ethics, 2012)
This research examines benevolent leadership and makes three key contributions to organizational research. The first contribution is a theoretical one; the development of a theory-grounded conceptual model of benevolent leadership based on four streams of creating common good in organizations: morality, spirituality, vitality, and community. The second contribution is the development of an instrument (Benevolent Leadership Scale) to measure the construct of benevolent leadership. This scale is composed of four dimensions: Ethical Sensitivity, Spiritual Depth, Positive Engagement, and Community Responsiveness. The third contribution is of empirical nature: the exploration of potential outcomes of benevolent leadership in organizations, affective commitment, and organizational citizenship behavior.